The continuum of monocyte phenotypes: Experimental evidence and prognostic utility in assessing cardiovascular risk. Issue 6 (30th March 2018) - Cignarella, Andrea; Tedesco, Serena; Cappellari, Roberta; Fadini, Gian Paolo
Abstract: The monocyte–macrophage cell lineage represents a major player in innate immunity, and is involved in many physiologic and pathologic conditions. Particularly, monocyte–macrophages play a very important role in atherosclerosis and cardiovascular disease. Monocyte heterogeneity is well recognized but the biologic and clinical meaning of the various monocyte subtypes is not entirely understood. Traditionally, monocytes can be divided in classical, intermediate, and nonclassical based on expression of the surface antigens CD14 and CD16. While macrophage diversity is now well recognized to organize as a continuum, monocyte subsets have long been considered as separated entities. However, mounting evidence obtained by tracking the ontology of human monocytes help clarifying that monocytes mature from classical to nonclassical ones, through an intermediate phenotype. This concept is therefore best depicted as a continuum, whereas the subdivision into discrete CD14/CD16 subsets appears an oversimplification. In this review, we discuss the evidence supporting the existence of a monocyte continuum along with the technical challenges of monocyte characterization. In particular, we describe the advantage of considering monocytes along a continuous distribution for the evaluation of cardiovascular risk. We make the point that small transition along the monocyte continuum better reflects cardiovascular risk than a simplified analysis of discrete monocyte subsets. Recognizing the monocyte continuum can be helpful to model other pathophysiologic conditions where these cells are involved. Abstract : Small transition along the monocyte continuum better reflects cardiovascular risk than a simplified analysis of monocyte subsets based on expression of the surface antigens CD14/CD16.